Решите уравнение : (2x-1)^2=3x^2-4x+17 : найдите значение выражения корень из x^2-2x+1 при x=2013 ; решите неравенство 3х^2-6x+1> либо равно x^2-x-1

Teddy62711 Teddy62711    2   19.05.2019 14:00    0

Ответы
Lero4ka222 Lero4ka222  12.06.2020 17:50

(2x-1)^2=3x^2-4x+17

4x^2-4x+1=3x^2-4x+17

4x^2-4x+1-3x^2+4x-17=0

x^2-16

x^2=16

x1=4

x2=-4

 

 

 x^2-2x+1 при x=2013

(x-1)^2=(2013-1)^2=2012^2=4048144

 

 решите неравенство 3х^2-6x+1>либо равно

 3х^2-6x+1=> x^2-x-1 3х^2-6x+1-x^2+x+1>=0 2x^2-5x+2>=0 D=(-5)^2-4*2*2=25-16=9=3^2 x1=(-(-5)+3)/2*2=8/4 x1=2 x2=(-(-5)-3)/2*2=2/4 x2=0,5

 

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра